Significant Correlation between Regional Tissue Oxygen Saturation and Vital Signs of Critically Ill Infants - Massa-Buck, Beri; Amendola, Virginia; McCloskey, Reagan; Rais-Bahrami, Khodayar (Frontiers in Pediatrics, 2017)
Background Near-infrared spectroscopy (NIRS) has been used to non-invasively measure specific tissue oxygen saturation (StO2) continuously. Cerebral autoregulation status can be derived from NIRS and arterial blood pressure. The relationship of both cerebral and somatic StO2, fractional tissue oxygen extraction (FTOE), and cerebro-splanchnic oxygenation ratio (CSOR) with measured vital sign parameters for Neonatal Intensive Care Unit (NICU) patients has not been well studied. Objective The aims of this study are to determine if significant relationships of brain and somatic StO2, brain and somatic FTOE, and CSOR parameters with vital signs for neonates exist and assess relationship between pressure passivity index, cerebral autoregulation, and mean blood pressure (MBP). Design/methods Neonates weighing < 5 kg, preferentially with an arterial catheter, were enrolled in the study. FORE-SIGHT Elite (CASMedical Systems, Inc., Branford, CT, USA) cerebral and somatic NIRS sensors were placed over the abdominal right upper quadrant and right frontal-temporal area of the forehead for 24 h. Vital signs including arterial MBP were recorded simultaneously from the patients’ bedside monitor. Data were averaged into 60 s windows and analyzed using linear regression. Results were stratified by gestational age (GA), birth weight (BW), and presence of brain abnormality. Results Data were obtained from 27 subjects (GA 22.2–42 weeks). Two subjects did not have an arterial line, thus they were not included in the MBP measurements. There were ~28,000–31,000 paired data points per comparison. Significant positive and negative correlations (p value < 0.0001) were noted between NIRS parameters and vital signs. When stratified by BW, there was a positive correlation between brain StO2 (StO2B) and MBP in the <1,500 g BW group (r = 0.193) and a negative correlation in >1,500 g group (r = 0.057). Brain and somatic FTOE in <1,500 g BW revealed a negative correlation with MBP (r = 0.172 and r = 0.086, respectively). In patients with an abnormal brain scan, a positive correlation was noted between StO2B and MBP (r = 0.354), and a negative correlation was noted between FTOE-B and MBP (r = 0.305). Generated pressure passive index plots suggested good cerebral autoregulation at low normal MBP ranges for lower weight and GA subjects. Conclusion There is a significant correlation between cerebral and somatic StO2 and FTOE with measured vital sign parameters in NICU patients.